2019
DOI: 10.4314/njb.v36i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in Amaranth (<i>Amaranthus</i> spp.) based on phenotypic and RAPD markers

Abstract: Genetic similarities, which can be detected with phenotypic and molecular markers, are important for effective use of available germplasm. It provides information on genetic diversity for reliable gene recombination. Thirty accessions of amaranth were assessed for variation with 15 phenotypic characters and 10 random amplified polymorphic DNA (RAPD) primers. Significant (p < 0.05) phenotypic variation was observed among the accession at the vegetative phase and most of the accessions had leaves with green pigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Thus, there is a vast potential for genetically improving vegetable amaranths, harnessing their heterogeneity. Studies demonstrated substantial variability among A. hybridus and its sister species, reflected in both agronomic and qualitative traits [36][37][38][39][40][41]. All the traits examined in this study showed a remarkable variation in all the cultivars and significantly influenced leaf and seed yield.…”
Section: Discussionmentioning
confidence: 63%
“…Thus, there is a vast potential for genetically improving vegetable amaranths, harnessing their heterogeneity. Studies demonstrated substantial variability among A. hybridus and its sister species, reflected in both agronomic and qualitative traits [36][37][38][39][40][41]. All the traits examined in this study showed a remarkable variation in all the cultivars and significantly influenced leaf and seed yield.…”
Section: Discussionmentioning
confidence: 63%
“…Genetic similarities were also important for the effective use of available germplasm by using phenotypic and molecular markers. Amaranth accessions were assessed for variations using random amplified polymorphic DNA (RAPD) primers ( 24 ) for getting information on genetic diversity for reliable gene recombination. For carrying out a successful hybrid program, analysis of phenotypic diversity and traits is very valuable.…”
Section: Breeding Behavior and Approachesmentioning
confidence: 99%
“…These crops can be grown in most countries' environmental conditions and are easily available plant sources of micronutrients to alleviate micronutrient malnutrition ( 21 ). There is a need for their genetic improvement and to explore the breeding behavior of these crops, possibilities to create variations in population, and the use of molecular markers to study diversity in amaranth and quinoa ( 22 24 ) ( Table 3 ). We have reviewed genetic mapping studies and DNA barcoding to understand the gene sequence of these crops ( Table 3 ).…”
Section: Introductionmentioning
confidence: 99%